2017
DOI: 10.18585/inabj.v9i3.298
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polysaccharides Peptides Ganoderma Lucidum to Aortic Foam Cell Count and Lipid Profile in Type 2 Diabetic Model Rattus Norvegicus Strain Wistar

Abstract: B ACKGROUND: Type 2 Diabetes Mellitus (DM)is one of dominant factors in cardiovascular deaths and induces endothelial dysfunction. A definite sign of endothelial dysfunction is foam cells formation derived from oxidized LDL. This study was conducted to determine the effect of Polysaccharides Peptides (PsP) Ganoderma lucidum to foam cell counts and lipid profile in diabetic model rats with high-fat diet. METHODS:Treatment group was categorized to negative control, positive control, DM-50, DM-150, and DM-300. Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…( 25) A previous study demonstrated that β-1,3/1,6-Dglucan from mycelia extract acts as an immunomodulator and reduces the inflammatory response to obesity due to consumption of a high-fat diet. (12,26) These findings provide potential treatment of obesity by using traditional medicine. In line with previous findings, the results of our study showed that b-1,3/1,6-D-glucan was able to counteract the negative effects of obesity and maintain normal kidney function.…”
Section: Discussionmentioning
confidence: 88%
“…( 25) A previous study demonstrated that β-1,3/1,6-Dglucan from mycelia extract acts as an immunomodulator and reduces the inflammatory response to obesity due to consumption of a high-fat diet. (12,26) These findings provide potential treatment of obesity by using traditional medicine. In line with previous findings, the results of our study showed that b-1,3/1,6-D-glucan was able to counteract the negative effects of obesity and maintain normal kidney function.…”
Section: Discussionmentioning
confidence: 88%
“…Studies in GLPP has shown that treatment of GLPP decreased the levels of inflammatory cytokines in atherosclerotic mice model (23), atrial fibrillation (24), dyslipidemic and high risk coronary heart disease patients (25). Current results showed that hsCRP, and TNF-α were significantly decreased in both control and treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…As a traditional Chinese herbal medicine, G . lingzhi has many pharmaceutical effects, such as immunomodulatory activity [ 4 , 5 ], regulation of cardiovascular function [ 6 , 7 ], regulation of blood glucose [ 8 , 9 ], and a hepatoprotective effect [ 10 , 11 ]. Ganoderma are particularly recommended for their immune-supporting effects [ 2 ], and the medicinal evidence comes from both animal experiments [ 11 , 12 ] and clinical trials [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%